Working International Meeting in Ljubljana (Slovenia) about Modern Phraseology as a Vital Linguistic Scientific Field - Žele, Andreja (Slavistica Vilnensis, 2022)
On December 16, 2022, a bilateral Slovenian-Croatian phraseology working meeting was held at the Faculty of Arts of the University of Ljubljana, at which the state of phraseology in Slovenia and Croatia was updated in a very concise manner. The organizer was the Faculty of Arts in Ljubljana and, within this institution, the Department of Slovene Studies. The expert discussion took place according to thematic blocks, namely: 1) Methods, approaches and reviews, 2) Phraseology in dictionaries, 3) Teaching and learning phraseology, and 4) Current phraseological research. It has been confirmed that such working international meetings with the much-needed exchange of expert opinions and experiences are necessary for the smooth development of the profession and at the same time are also invaluable for their vision within the wider linguistic activity.